Bacterial hypothetical proteins may be of functional interest - Vincent, Antony T. (Frontiers in Bacteriology, 2024)
Genomic analysis is part of the daily routine for many microbiology researchers. These analyses frequently unveil genes that encode proteins with uncertain functions, and for many bacterial species, these unknown genes constitute a significant proportion of their genomic coding sequences. Because these genes do not have defined functions, they are often overlooked in analyses. Experimentally determining the function of a gene can be challenging; however, ongoing advancements in bioinformatics tools, especially in protein structural analysis, are making it progressively easier to assign functions to hypothetical sequences. Leveraging various complementary tools and automated pipelines for annotating hypothetical sequences could ultimately enhance our comprehension of microbial functions and provide direction for new laboratory experiments.